Temperature Adaptability of Asphalt Pavement to High Temperatures and Significant Temperature Differences - Xueying Zhao; Aiqin Shen; Baofu Ma (Advances in Materials Science and Engineering)
Temperature adaptability of asphalt pavements is very important, due to their potential influence on pavement structure design, particularly in areas that experience significant temperature differences. In this paper, a finite element (FE) model was developed, and Turpan-Xiaocao Lake Highway in southern Xinjiang was taken as a case study engineering, which tends to experience this adverse environmental condition (temperature difference: 25.5°C; July 14, 2008). In this model, the generalized Kelvin model and the Burgers model were used. The time-dependent tire pressure was considered. To guide pavement structure design and control pavement distresses in this area, seven alternative pavement structures were selected to simulate and analyze pavement temperature fields and the mechanical responses. It was observed that the influence of air temperature had the greatest impact on Str-1, possibly due to the thinnest asphalt course. Moreover, when rutting depth, maximum shear stress of the asphalt course, deflection on the pavement surface, and compressive strains at the subgrade top surface were taken as the evaluation indices, the adaptability of asphalt pavements using compound base courses had obvious advantage due to their strong absorption and reflection of load impact. The adaptability of seven structures analyzed in this paper decreased in the following order: Str-5 > Str-6 > Str-4 > Str-2 > Str-m > Str-1 > Str-3. In addition, it broke the traditional view that asphalt pavement with a flexible base had the poor ability on rutting resistance. Besides, it also suggests that when the thickness of asphalt courses was equivalent, increasing the thickness of chemical-treated base courses would help with the deformation resistance, and vice versa.